Evaluating Populus tremula L. and Salix caprea L. for phytoremediation: growth, metal uptake, and biochemical responses under arsenic, cadmium, and lead stress - Sirgedaitė-Šėžienė, Vaida; Striganavičiūtė, Greta; Šilanskienė, Milana; Kniuipytė, Inesa; Praspaliauskas, Marius; Vaškevičienė, Irena; Lemanas, Egidijus; Vaitiekūnaitė, Dorotėja (Frontiers in Plant Science, 2025)
This study investigates the phytoremediation potential of Populus tremula L. and Salix caprea L. in response to As, Cd, and Pb exposure using hydroponics. Seedlings were exposed to 5–50 µM Cd, 100–1000 µM As, and 50–200 µM Pb in P. tremula, and to 5–50 µM Cd, 25–100 µM As, and 200–600 µM Pb in S. caprea. By analyzing growth, heavy metal(loid) (hereafter referred to as ‘metals’) uptake, biochemical markers (phenolics, soluble sugars, lipid peroxidation, antioxidant enzymes), and shifts in elemental (P, S, Mg, K, Ca, Mn, Zn, Cu, Fe) composition, this study provides a comprehensive evaluation of these species response to metal contamination at the seedling stage. Distinct dose- and metal-specific responses were observed, with Pb exposure inducing enhancing growth effects (height increase up to 27%, total chlorophyll increase up to 67%) and hormesis at low to moderate concentrations (equivalent to 200 µM of Pb(NO3)2), while Cd and As reduced growth in both species. Biochemical analyses revealed significant impacts on the antioxidant activity in response to metal stress, with differences in the involvement of enzymatic vs. non-enzymatic defenses, i.e., an initial enzymatic response, and a shift towards secondary metabolite production under prolonged or severe stress. S. caprea exhibited higher translocation of Cd (0.77 at 5 µM), suggesting its potential for phytoextraction, while both species demonstrated strong phytostabilization capacity for Pb (up to 0.54% of Pb in root DW). Nutrient homeostasis disruptions were observed, with both species showing altered nutrient uptake and distribution, e.g., co-accumulation of Cd and Zn, with Zn increase up to 639% in Cd-treated S. caprea (50 µM). These results offer valuable insights into the biochemical mechanisms underlying heavy metal tolerance in P. tremula and S. caprea, while suggesting directions for future studies on the real-world applicability of phytoremediation strategies.